The Role of Sharia Financial Management in Supporting School Program Innovation at Warasansart Lammai School Thailand - Irma Damayanti Simanjuntak; Isra Hayati (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study addresses the challenge of ensuring sustainable and accountable school management through Sharia-based financial principles amid limited institutional resources. It aims to evaluate the role of Sharia-based financial management and program innovation at Warasansart Lammai School, Thailand. A qualitative descriptive approach was employed, with data collected through observations, in-depth interviews with the school principal, teachers, and administrative staff, and document analysis. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. To ensure validity and reliability, source and method triangulation were applied. The findings reveal that the implementation of Sharia-based financial management significantly supports the sustainability, transparency, and effectiveness of innovative educational programs. However, the school continues to encounter constraints related to limited financial resources and infrastructural facilities. This study contributes to the discourse on Islamic educational management by offering an empirical model for integrating Sharia financial principles with institutional innovation in faith-based schools.